Rejuvenation of City Gateway as the Identity of Medan - Dwi Lindarto Hadinugroho; Eunice Ananda Putri Matondang (International Journal of Architecture and Urbanism, 2020)
As a developing city, Medan carries out a significant role in establishing the identity and image of the city and the development of the surrounding cities and districts. One effort to establish the identity and image of the city can be created through the existence of city gates that can produce a plot, rhythm, and balance for the city bounded. The gate of Medan City has not succeeded in becoming a city gate that meets the needs needed by migrants who pass through the city gate area. This study will address the problems discovered at the Medan City gate in Binjai, Tanjung Morawa, Tembung, and Pancur Batu and relate them to the rejuvenation of the city area through revitalization methods in supporting Metropolitan Mebidangro. The research aims to analyze predetermined variables, namely elements of the city image, namely path, edge, district, nodes, and landmark. For this reason, a qualitative descriptive study was carried out, which was realized through observation and interviews and also documentation studies. The results of the research obtained from this study can be used as a reference and solution to find out the problems that exist int the area around Medan City gate and also give functional supports to develop the area around Medan City.